Diagnostic Accuracy of Neonatal Sepsis Scoring Systems in Preterm Infants - Rudy, Rudy; Huda, Mega Hasanul; Chodidjah, Siti (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Neonatal sepsis remains a major cause of morbidity and mortality among preterm infants, particularly in low- and middle-income countries. Early identification through clinical scoring systems, such as the Singh Score, Rosenberg Score, and Bekhof Score, may improve diagnostic accuracy and support timely management. This study aimed to systematically evaluate the diagnostic performance of these three clinical scoring instruments in detecting neonatal sepsis. A systematic search was conducted across seven electronic databases from inception to August 2025. Studies assessing the diagnostic accuracy of the selected scoring systems were included, critically appraised, and analyzed. Data on sensitivity, specificity, and other diagnostic accuracy measures were extracted and synthesized. Five eligible studies were identified, most of which were conducted in low- and middle-income countries, with sample sizes ranging from 80 to 658 neonates. The pooled sensitivity of the three instruments ranged from 0.56 to 0.76, with the Singh Score demonstrating the highest sensitivity (76%), followed by the Bekhof (63%) and Rosenberg (56%) scores. The pooled specificity ranged from 0.33 to 0.69, indicating low to moderate ability to exclude non-sepsis cases. Overall, these instruments demonstrate moderate sensitivity but limited specificity and are more suitable for ruling out sepsis rather than definitively confirming the diagnosis. Their use should be integrated with comprehensive clinical assessment and additional laboratory investigations. These scoring systems may aid in risk stratification and help reduce unnecessary treatment by identifying neonates at low risk of sepsis.Keywords: neonatal sepsis; preterm infants; clinical scoring system; diagnostic accuracy